A Biblical Evaluation of O. R. L. Crosierâ€™s View of Atonement - Donny Chrissutianto (Fakultas Filsafat Universitas Advent Indonesia, 2023)
The idea of when Jesus does His atonement has been a discussion between Protestants and Seventh-day Adventists. Evangelicals have thought that Adventists do not believe that the cross is a complete atonement of God. This question was raised in 1957 and Adventists answered it through Questions on Doctrine. This question, once believed by some Adventist pioneers, has its foundation in the writing of O.R.L. Crosier. This article aims to answer biblically why Crosierâ€™s idea is rejected in this denomination. Using the word study of â€œatonement,â€ this work argues that the biblical idea of atonement involves the sacrifice and the application of the high priest in the sanctuary. The Old and New Testaments embrace the concept that Jesus died on Calvary and His application ministry in the heavenly sanctuary as atonement. The reason for Crosierâ€™s limited perception of atonement since he focused on the work of the priest and was not on the overall idea of atonement in the Bible.